The right to housing as a component of the right to an adequate standard of living: issues of implementation amidst Ukraine’s housing stock destruction and solutions - V. V. Maltsev (Bulletin of Kharkiv National University of Internal Affairs)
This article presents a comprehensive analysis of the right to housing, framing it as an essential component of the broader right to an adequate standard of living. Situated within the context of international human rights norms, the article scrutinizes how these global standards influence and shape Ukrainian legislation. It argues that national laws should aim not merely to provide a basic minimum but to ensure a dignified standard of living that encompasses the full range of capabilities necessary for individuals to function effectively in society.